Long-Term Outcome of Pediatric-Onset MS - J. Gordon Millichap (Pediatric Neurology Briefs, 2013)
Researchers at University Hospital of Wales, Cardiff; and University of Bristol, UK studied the clinical features and disability in pediatric-onset multiple sclerosis (POMS) in a population-based cohort with long-term follow-up, and compared to a cohort of patients with adult-onset (AOMS) disease.